Biomechanical characteristics of immediately loaded and osseointegration dental implants inserted into Sika deer antler. (September 2018) - He, Yun; Hasan, Istabrak; Keilig, Ludger; Fischer, Dominik; Ziegler, Luisa; Abboud, Markus; Wahl, Gerhard; Bourauel, Christoph
Highlights: Density of antler tissue around implants increased under immediate loading. Density of antler tissue around osseointegrated implants were in a similar range. The density and geometry of antler tissue influenced the biomechanical values. Sika deer antler is a promising alternative in implant biomechanical studies. Abstract: This study aimed to compare biomechanical characteristics of immediately loaded (IL) and osseointegrated (OS) dental implants inserted into Sika deer antler and lay a foundation for developing an alternative animal model for dental implants studies. Two implants per antler were inserted. One implant was loaded immediately via a self-developed loading device; the other was submerged and unloaded as control. IL implants were harvested after different loading periods. The unloaded implants were collected after OS and the shedding of antler. Specimens were scanned by µCT scanner and finite element models were generated. A vertical force of 10 N was applied on the implant. The mean values of maximum displacements, stresses and strains were compared. The results showed that the density of antler tissue around the implants dramatically increased as the loading time increased. After shedding the antler, 3 pairs of antlers were collected and the density of antler tissue remained in a similar value in all specimens. The maximum values of displacement and stresses in implant and stresses and strains in antler tissue were significantly different among OS models. In one antler, all the biomechanical parameters of IL model were significantly higher than those of OS model of the same animal ( P  < 0.05) and wider distributions were obtained from IL model. It can be concluded that implants inserted into Sika deer antler might not disturb the growth and calcification process of antler and the use of Sika deer antler model is a promising alternative for implant studies that does not require animal sacrifice.